Cord blood prolidase activity correlates with gestational age and birth weight - Kurt, A. Nese Citak; Ustundag, Bilal; Akarsu, Saadet; Kurt, Abdullah; Yilmaz, Erdal; Ocal, Cesur; Aygun, A. Denizmen (Karger, 2008)
Background: Prolidase, a specific iminopeptidase involved in collagen turnover, is especially active in growing tissues. Objectives: To investigate the relationship between cord blood prolidase activity and both birth weight and gestational age. Methods: Cord blood was collected consecutively from 50 healthy newborns (35 term, 15 preterm). Prolidase activity was measured in the samples using standard methods. Results: The mean 8 SD cord blood prolidase activity was 41.4 +/- 6.9 U/l in term infants and 35.2 +/- 8.0 U/l in preterm infants and these were significantly different (p < 0.01). There were positive correlations between cord blood prolidase and both birth weight (r = 0.533, p < 0.01) and gestational age (r = 0.806, p < 0.01). Conclusion: Cord blood prolidase activity may be a good indicator of fetal maturation and gestational age. Copyright (C) 2008 S. Karger AG, Basel.
Keywords: prolidase; cord blood; birth weight; gestational age